2021
DOI: 10.1016/j.radonc.2021.01.016
|View full text |Cite
|
Sign up to set email alerts
|

Spirometer-guided breath-hold breast VMAT verified with portal images and surface tracking

Abstract: Background and purpose: Fast rotating closed-bore gantry linacs are ideally suited for breath-hold treatments due to reduced imaging and delivery times. We evaluated the reproducibility and stability of spirometer-guided breath-hold breast treatments, using intra-bore surface monitoring and portal imaging on Halcyon (Varian Medical Systems). Materials and methods: Seven left-sided breast cancer patients were treated in breath-hold using the SDX spirometer (Dyn'R) with an integrated boost volumetric arc protoco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…Monitoring was initiated within two seconds after execution of the couch shift. This surface scanning system is described in detail in Delombaerde et al [16,19] but the basics are reiterated here. The system consists of two Kinect™ for Windows cameras (Microsoft, Redmond, VA, USA) mounted at the back of the Halcyon bore to image the patient while at the treatment isocenter.…”
Section: Surface Scanning Acquisitionmentioning
confidence: 99%
See 2 more Smart Citations
“…Monitoring was initiated within two seconds after execution of the couch shift. This surface scanning system is described in detail in Delombaerde et al [16,19] but the basics are reiterated here. The system consists of two Kinect™ for Windows cameras (Microsoft, Redmond, VA, USA) mounted at the back of the Halcyon bore to image the patient while at the treatment isocenter.…”
Section: Surface Scanning Acquisitionmentioning
confidence: 99%
“…Due to limited access to the patient by the radiotherapy technologists (RTT) inside the bore, patient setup is performed in front of the linac after which the couch automatically translates to the treatment isocenter. Setup can be performed either guided by the built-in lasers or using a surface scanning system [15,16], however after translation to the treatment isocenter, the patient falls outside the reach of the ceilingmounted surface monitoring systems [17,18]. To investigate the potential added value, we have developed an intra-bore surface scanning system to monitor patient motion during treatment [16,19] to be able to assess motion during the image guidance (IGRT) procedures (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For VMAT delivery there are further challenges as the anatomy projected in the BEV will change with gantry angle, and treatment planning system (TPS) optimisers typically provide MLC patterns that obscure a larger portion of the BEV. One group [15] has utilised EPID imaging on a closed-bore linac for analysing breast VMAT DIBH treatments at a single gantry angle with manual registration to extract the CW position. This approach is limited as monitoring of the CW position is only performed for a small number of time points during the treatment and the reported CW position may be subject to inter-user variability during manual registration.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Deep inspiration expands the lung and displaces the upper abdominal organs away from the chest wall. The quality of DIBH is currently assessed by various techniques,for example,by tracking an external marker block placed on the patient's chest or abdomen, 3 by monitoring the patient's skin surface with optical surface monitoring systems, 4 by controlling the breathing, 5,6 or by employing the treatment room lasers and tattoos on the patient's abdomen. 7 A low-cost in-house system for monitoring DIBH with an industrial laser distance meter was reported by Jensen et al 8 All such systems have in common is that they are not assessing the clinically relevant part of the patient's anatomy but a more or less motion correlated surrogate.…”
Section: Introductionmentioning
confidence: 99%